Chlorpyrifos-induced changes in oxidant/antioxidant status and haematological parameters of Cyprinus carpio carpio: Ameliorative effect of lycopene - Ural, Mevlut Sener (Pergamon-Elsevier Science Ltd, 2013)
The present study was carried out to investigate the potential ameliorative effects of lycopene against chlorpyrifos (CPF) toxicity in carp. The fish were divided into 7 different experimental groups and received the following treatments: Group 1, control; Group 2, orally administered corn oil; Group 3, oral lycopene (10 mg kg(-1) body weight); Group 4, exposure to 0.040 mg L-1 CPF; Group 5, exposure to 0.040 mg L-1 CPF plus oral administration of 10 mg kg(-1) lycopene; Group 6, exposure to 0.080 mg L-1 CPF; and Group 7, exposure to 0.040 mg L-1 CPF plus oral administration of 10 mg kg(-1) lycopene. Treatment was continued for 14 d and samples of the blood and tissue (liver, kidney, and gill) were collected at the end of the experiment and analysed for their oxidant-antioxidant status, including the malondialdehyde (MDA) levels, and the superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px) activity. The samples were also measured for changes in the haematological parameters, such as the red blood cell (RBC) and white blood cell (WBC) counts, the haemoglobin concentration (Hb), the haematocrit (Ht) level, and the erythrocyte indices: the mean corpuscular volume (MCV), the mean corpuscular haemoglobin (MCH) and the mean corpuscular haemoglobin concentration (MCHC). The findings of this study demonstrated that CPF had a negative effect on the haematological parameters and the antioxidant enzyme activities of the fish; this toxic effect was neutralised by the administration of lycopene. The present results suggest that lycopene (10 mg kg(-1)) can be effective in the protection of CPF-induced toxicity in fish. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Pesticides; Chlorpyrifos; Lycopene; Haematology; Oxidative stress; Fish